Off the grid Christmas - Porter, Mary Ellen (Love inspired suspense. Larger print., 2017)
When computer expert Arden DeMarco hacks secret files and discovers evidence of treason, a price is put on her head. What started as a mission to help a friend is now a fight for her life with assassins and the FBI tracking her down. There's no time to get distracted by her brother's best friend, Kane Walker, but the security expert promised Arden's family he'd bring her safely home for the holidays. Instead they're dodging bullets--and fighting their growing feelings--while Arden races to break the encryption and find out what's hidden in the files she stole. But as they're hunted by armed henchmen determined to make sure those secrets are never uncovered, keeping Arden safe is the only Christmas gift that matters.